Effect of various black nightshade (Solanum nigrum L.) fruit extract concentrations on maize (Single cross 704) seed germinability and vigour by standard germination test - اشکان عباسیان; آیدین حمیدی; لیلا یاری; اعظم دشتی (علوم و فناوری بذر ایران)
Contamination of maize seed production fields by blacknightshade weed is one of the seed production problems in Moghan region. With attention to possible effect of black nightshade fruit extract on maize seed germination properties, effect of various fruit extract concentrations including; 10, 30, 50, 70 and 100% and control (seeds not soaked in black nightshade fruit extract) on maize (Single cross 704) seed germinability and vigor were evaluated. The experiment was laid out as a completely randomized design with four replications. Studied characters consisted of: germinated seeds number two and three days after planting, normal and abnormal seedlings number, ungerminated seeds number, mean time to germination, coefficient of velocity of germination, mean daily germination, daily germination speed, seedling and primary shoot and root length, primary shoot and root fresh and dry weight and seedling length and weight vigour indices. The results showed that extract concentrations had not significant effect on germinated seeds number three days after planting, normal and abnormal seedlings number, ungerminated seeds number, mean daily germination and daily germination speed. While extract concentrations significantly increased germinated seeds number two days after planting, mean time to germination, coefficient of velocity of germination, seedling and primary shoot and root length, primary shoot and root fresh and dry weight and seedling length and weight vigor indices. By increasing of blacknightshade extractconcentration, most of the positive seed germination and seedling vigor indices increased